The dimensions of affective attachment as predictors of the level of emotiona intelligence - Đorđević, Tamara S (Sinteze - časopis za pedagoške nauke , književnost i kulturu, 2017)
The core issue of this investigation was to examine whether the dimensions of familial affective attachment (anxious and avoidant) can serve as predictors of the level of emotional intelligence in university students. In addition, explored was the connection between the above constructs, as well as whether they differ in prominence by sex, year of study, academic success, birth order and parent’s education. The prominence of the dimensions of familial affective attachment on the sample used was also investigated. The findings show that emotional intelligence in general, as well as its Ability to Name and Express Emotion can be predicted on the basis of dimensions of Anxiety and Avoidance. The prominence of dimensions of familial attachment is low in the sample, and the Secure pattern of attachment predominates. Differences in the prominence of constructs under observation were not found by sex, year of study, birth order and parent’s education, while connection between academic success and emotional intelligence is positive.The findings concerning connection between dimensions of familial affective attachment and capability of emotional intelligence show that the dimension Avoidance is negatively correlated with the Ability to Name and Express Emotion.